2014
DOI: 10.1111/joop.12089
|View full text |Cite
|
Sign up to set email alerts
|

Which employees craft their jobs and how? Basic dimensions of personality and employees' job crafting behaviour

Abstract: The aim of the current research was to examine to what degree basic personality dimensions serve as determinants of job crafting behaviour and to investigate how this behaviour can be influenced via behavioural intentions. In Study 1, we investigated the relationship of approach and avoidance temperament with job crafting in terms of seeking resources, seeking challenges, and reducing demands in a sample of 193 international employees. In Study 2 (n = 130 employees), we experimentally manipulated the current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 75 publications
7
93
1
8
Order By: Relevance
“…Our present findings suggest students higher in mastery approach orientation also have higher workload -but this higher workload does not appear to distract students from proactive career behaviours. As Bipp and Demerouti (2015) reported, people who are high in approach temperament tend to seek both resources and demands. We can also conclude that reducing students' workload is unlikely to make them engage in more proactive career behaviours, and therefore should not form the basis of employability interventions.…”
Section: Discussionmentioning
confidence: 98%
“…Our present findings suggest students higher in mastery approach orientation also have higher workload -but this higher workload does not appear to distract students from proactive career behaviours. As Bipp and Demerouti (2015) reported, people who are high in approach temperament tend to seek both resources and demands. We can also conclude that reducing students' workload is unlikely to make them engage in more proactive career behaviours, and therefore should not form the basis of employability interventions.…”
Section: Discussionmentioning
confidence: 98%
“…With regard to individual differences, as would be expected, individuals high in approach temperament and promotion‐focus—who are people motivated to obtain positive end‐states (Elliot & Thrash, 2002; Higgins, )—tend to engage in more approach crafting (Bipp & Demerouti, ; Lichtenthaler & Fischbach, ; Rudolph et al, ). Unexpectedly, meta‐analytic studies also found a weak yet positive relationship between prevention‐focus and approach crafting (Lichtenthaler & Fischbach, ; Rudolph et al, ).…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 98%
“…2016). JD-R modeli bakış açısıyla iş becerikliliği; fiziksel, örgütsel ya da sosyal düzeyde iş taleplerini (örn; ağır işyükü ve zaman baskısı) ve iş kaynaklarını (örn; özerklik ve geribildirim) dengelemek amacıyla işin özelliklerinde gerekli değişimleri gerçekleştirme faaliyetidir (Bipp ve Demerouti, 2015). Model doğrultusunda iş becerikliliği davranışları çalışanların iş kaynaklarını artırırken, iş taleplerini en düşük düzeye taşımakta ve iş talepleri ile kaynaklarını dengelemektedir (Ingusci vd.…”
Section: İş Becerikliliği (Job Crafting)unclassified
“…Örneğin Petrou ve arkadaşları (2012) ve Bipp ve Demerouti (2015) 3 (üç) ayrı iş becerikliliği davranışı tanımlamış ve bu davranışları şu şekilde ifade etmiştir: a-Kaynak arama: Geribildirim ya da bilgi sağlayıcı davranışları ifade eder (örn; iş arkadaşlarından ve yöneticilerden tavsiye istemek, iş performansına ilişkin geribildirim istemek), b-İşin zorlayıcı olmasını isteme: İşte motive olmak için iş taleplerinde değişiklikler yapmaktır (örn; işe ilişkin daha fazla sorumluluk almak, yeni görevler istemek), c-Talepleri azaltma: İşte duygusal, zihinsel ve fiziksel talepleri minimize etmeyi ve işyükü ve zaman baskısını azaltmayı içerir (örn; iş yükü yönünden çok zorlayıcı bir işi hafifletmek).…”
Section: İş Becerikliliği (Job Crafting)unclassified
See 1 more Smart Citation